Teaching maintenance of medical devices in simulation centers: a pilot study - Quiroga Torres, Daniel Alejandro; Presiga, Ana Maria; Flórez Luna, Nestor; Cruz, Antonio Miguel (Springer Verlag, 2016)
This paper aims to measure what the students’ perceived learning outcome achievements are after finishing medical devices courses I and II. This is a pre- post-test with no control group study design. Twenty-four students doing medical devices courses I and II with a test in the simulation center of a Biomedical Engineering Program participated in this pilot study. A paper-based survey composed of a demographic and 5-point Likert (“1” is strongly disagree and “5” is strongly agree) measured the students’ perceived learning outcome achievements after exposing them to medical devices courses. A Wilcoxon signed-rank test and Mann-Whitney U Test statistics were conducted to test the two hypotheses of this study. Our analysis showed statistically significant results between the pre-survey sum mean and SD: 7.50, 1.31; and between the post-survey mean and SD: 8.56, 1.15, p=0.015, indicating the students’ perceived learning outcome achievements after putting them through medical devices courses I and II had significantly improved by the end of the courses. Also, no statistically significant results were found between the post-survey mean and SD: 4.37, 0.57 learning outcome perceptions or between the students’ actual marks mean and SD: 4.58, 0.18, p=0.28), indicating no differences between what the students perceived they had learned compared with what they had really learned.

Este artículo tiene como objetivo medir cuáles son los logros de los resultados de aprendizaje percibidos por los estudiantes después de terminar los cursos de dispositivos médicos I y II. Esta es una prueba previa y posterior sin un diseño de estudio de grupo de control. En este estudio piloto participaron veinticuatro estudiantes de los cursos I y II de dispositivos médicos con una prueba en el centro de simulación de un Programa de Ingeniería Biomédica. Una encuesta en papel compuesta por datos demográficos y Likert de 5 puntos (“1” está totalmente en desacuerdo y “5” está totalmente de acuerdo) midió los logros de los resultados de aprendizaje percibidos por los estudiantes después de exponerlos a cursos de dispositivos médicos. Se realizaron una prueba de rango con signo de Wilcoxon y una prueba estadística de la prueba U de Mann-Whitney para probar las dos hipótesis de este estudio. Nuestro análisis mostró resultados estadísticamente significativos entre la media de la suma previa a la encuesta y la DE: 7,50, 1,31; y entre la media posterior a la encuesta y la DE: 8,56, 1,15, p = 0,015, lo que indica que los logros de los resultados de aprendizaje percibidos por los estudiantes después de someterlos a los cursos de dispositivos médicos I y II habían mejorado significativamente al final de los cursos. Además, no se encontraron resultados estadísticamente significativos entre la media posterior a la encuesta y la DE: 4,37, 0,57 percepciones de los resultados de aprendizaje o entre la media de las calificaciones reales de los estudiantes y la DE: 4,58, 0,18, p = 0,28), lo que indica que no hay diferencias entre lo que los estudiantes percibieron que habían aprendido en comparación con lo que realmente habían aprendido.
Keywords: Educación médica; Aprendizaje previo - Evaluación; Prior learning - Evaluation; Biomedical engineering; Engineering education; Medical devices; Simulation center; Ingeniería Biomédica; Educación en ingeniería; Dispositivos médicos; Centro de simulación